2020
DOI: 10.25304/rlt.v28.2404
|View full text |Cite
|
Sign up to set email alerts
|

Students’ video viewing habits during a flipped classroom course in engineering mathematics

Abstract: A flipped classroom lecture approach was utilised in an engineering mathematics course (118 students). This article reports on student viewing habits based on 104 videos over a period of 12 weeks. The video statistics indicate that many students waited until the last day before assignments to watch the required videos. There are also indications that the students would try to reduce the heavy workload induced by watching all videos on a single day by skipping videos perceived as less valuable. The data show a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 25 publications
(35 reference statements)
1
22
0
7
Order By: Relevance
“…Previous studies have shown that learner attention lapses during 50-minute in-person lectures, starting in the first 5-15 minutes [30]. Similarly, longer online videos were associated with more dropouts (participants stopped watching partway through) [31] and there was a strong negative correlation between the length of a video and how much of the video students watched in one sitting [32]. Splitting video lectures into smaller chunks and adding interactive components can enhance audience engagement [33].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that learner attention lapses during 50-minute in-person lectures, starting in the first 5-15 minutes [30]. Similarly, longer online videos were associated with more dropouts (participants stopped watching partway through) [31] and there was a strong negative correlation between the length of a video and how much of the video students watched in one sitting [32]. Splitting video lectures into smaller chunks and adding interactive components can enhance audience engagement [33].…”
Section: Discussionmentioning
confidence: 99%
“…Students prefer short videos, preferably about just one topic at a time (Fyfield et al, 2019;Long et al, 2016). However, long videos are watched, but not in one go (Nielsen, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…They appreciate these videos even more than pre-recorded high-quality lecture videos (Guo, Kim, & Rubin, 2014). However, a study from Norway (Nielsen, 2020) shows that long videos are watched, but in several rounds, not in one.…”
Section: Use Of Videos In the Flipped Classroommentioning
confidence: 99%
“…Shih and Tsai (2017) and Andujar (2020) also maintained that flipped learning leads to enhanced effectiveness of learning, learning motivation and learning interest. Finally, it is among the strategies utilized to develop various skills including personal skills, problem-solving, critical thinking, knowledge integration, communication skills, teamwork skills, leisure attitudes and the skills of autonomous learning (Molnar, 2017;Shih & Tsai, 2017;Nielsen, 2020;He et al, 2019;Gopalan, 2019;). This finding may be linked to the general premise that technology, with the use of flipped learning model, responds effectively to the needs of social science and humanities students.…”
Section: Englishmentioning
confidence: 99%
“…With regards to the flipped learning technology challenges, the majority of studies (e.g., Akcayir & Akcayir, 2018; Van-Alten et al, 2019;Lo et al, 2017;Gardner, 2015;Barral et al, 2018;Nielsen, 2020;Peterson, 2016;Yacout & Abou-Shosha, 2016;Wells & Holland, 2015;Koo et al, 2016;Velegol et al, 2015) The resulting analysis found that flipped learning positively enhanced the learning outcomes and other skills among students in the fields of social sciences and humanities.…”
Section: Englishmentioning
confidence: 99%